Making the biblical text: textual studies in the Hebrew and the Greek Bible - Himbaza, Innocent; Roth-Mouthon, Mary-Gabrielle (Orbis biblicus et orientalis, 2015)
From Deuteronomistic history to Nebiim and Torah / Thomas Romer -- The Tiberian vocalization and the edition of the Hebrew Bible text / Jan Joosten -- Die Tiqqune sopherim im Horizont der biblischen Textgeschichte - Theologische Korrekturen, literarische Varianten im alttestamentlichen Text und Textvielfalt: wie gehen sie zusammen? / Adrian Schenker -- "Dreissig Jahre war David alt, als er König wurde..." (2 Sam 5,4)- Literarische und textkritische Studie der Regierungsnotizen in den Samuelbüchern / Philippe Hugo -- Revisiting 2 Kings 13:14-21 (MT and LXX) - The transposition of a pericope and multiple literary editions in 2 Kings / Matthieu Richelle -- Du sacerdoce à la royauté: une suppléance hasmonéenne sur le trône de David selon le texte massorétique de Zacharie 6, 11-15? / Yohanan P. Goldman-- Masoretic text and Septuagint as witnesses to Malachi 1:1 and 3:22-24 / Innocent Himbaza -- The Book of Jeremiah and the Hebrew and Greek texts of Ben Sira / Armin Lange